USING TECHNOLOGY TO IMPROVE VOCABULARY ACQUISITION - Behruzkhon Yuldoshev Behzod ugli (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article explores the role of technology in enhancing vocabulary acquisition among English language learners. It examines the effectiveness of digital tools, mobile applications, online platforms, and multimedia resources in supporting vocabulary learning. The paper also analyzes cognitive and pedagogical perspectives, emphasizing how technology promotes motivation, autonomy, and long-term retention.